Bagaimanakah Persepsi Keterpercayaan Masyarakat terhadap Elit Politik? - Haryanto, Handrix Chris; Rahmania, Tia; Mubarok, Ahmad R.; Dopo, Agung B.; Fauzi, Hafil; Fajri, Erdizal (Faculty of Psychology, Universitas Gadjah Mada, 2015)
The aim of this study was to identify Jakarta residents’ perceptions on the trustworthiness of political elites. The study used qualitative content analysis method involving as many as 461 persons as subjects. These political elites referred to the members of the House of Representatives, members of the People’s Consultative Council, the president and the members of his governmental cabinet, political parties, people or groups involved in politics and those participating in managing the state. The top ten factors able to degrade people’s trust in political elites were identical with the subjects’ perception about lie (29.28%), corruption (14.75%), selfishness (8.24%), incompetence (6.07%), scandals (5.64%), irresponsibility (1.95%), abuse of power (1.52%), laziness (1.52%), lack of transparency (1,30%), and lack of firmness (0.22%). The description about political elites worth trusting concerned about their honesty (39.70%), accountability (12.80%), integrity (1280%), caring (8.89%), morality (6.29%), firmness (4.34%), competence (3.69%), transparency (1.74%), and wisdom (1.74%). The study concluded that the trustworthiness of political elites refers to their dispositions that are considered to have good motives and go with any prevailing norms.